Rancang Bangun Aplikasi Android pada Section Engineering di Head Office - Anis Choirunnisa; M. Ridwan Arif Cahyono; Margareta Shinta Herawati (Jurnal Instrumentasi dan Teknologi Informasi (JITI), 2026)
The manual process of submitting Work Order Forms (FPK) in the Engineering Section causes various obstacles such as late delivery, difficulty in recording, and low efficiency and data accuracy. This study aims to design and build a digital system in the form of a Kodular-based Android Application to make it easier for tenants to make work order requests to Engineering. The user interface is designed using the draw.io tool and the backend system uses PHP and MYSQL. This application allows users to access information and submit work requests practically through mobile devices. Test results show an increase in time efficiency of 70.36% and cost efficiency reaching 82.43% compared to the manual system. In addition, features such as the Complaint Form, Dashboard, Satisfaction Survey, Instructions and Profiles help speed up the user flow and minimize the risk of data loss. This system has also been tested using the black box method and shows good results. Thus, this digital system effectively supports digital transformation in engineering work processes.